Human targeted phenobarbital presents a poor substrate of gut microbiome deciphering new drug targets beyond pharmacokinetic curbs - Imran Mukhtar; Haseeb Anwar; Arslan Iftikhar; Heba E. Hashem; Qasim Ali; Farhan Siddique (BMC, 2022)
Abstract Background The gut microbiome, a new organ of the body, can potentially alter the pharmacokinetics of orally administered drugs through microbial enzymes. However, absorption of orally administered non-antibiotic drugs by the gut microbiome, during drug-microbiome interaction, is barely addressed. Structural homology studies confirm similar membrane transport proteins in gut epithelial cells and the gut microbiome of the host that may compete for drug substrates with the host itself for its absorbance. Therefore, it is hypothesized that orally administered human targeted phenobarbital may interact and/or be uptake by the gut microbiome during its transit through the small intestine. Methods In the current in vivo study, thirty-six male Wistar albino rats were divided into six groups including one control and 5 treatment groups, each having an equal number of rats (n = 6). Phenobarbital was administered orally (single dose of 15 mg/kg bw) to treatment groups. Animals were subsequently sacrificed to harvest microbial mass pallets residing in the small intestine after 2, 3, 4, 5, and 6 h of phenobarbital administration. Phenobarbital absorbance by the microbiome in the microbial lysate was estimated through RP-HPLC-UV at a wavelength of 207 nm. Results Maximum phenobarbital absorbance (149.0 ± 5.93 µg) and drug absorbance per milligram of microbial mass (1.19 ± 0.05 µg) were found significantly higher at 4 h of post-administration in comparison to other groups. Percent dose recovery of phenobarbital was 5.73 ± 0.19% at 4 h while the maximum intestinal transit time was 5 h till the drug was absorbed by the microbes. Such results pronounce the idea of the existence of structural homology between membrane transporters of the gut microbiome and intestinal enterocytes of the host that may competitively absorb orally administered phenobarbital during transit in the small intestine. The docking studies revealed that the phenobarbital is a poor substrate for the gut microbiome. Conclusion Gut microbiome may competitively absorb the non-antibiotics such as phenobarbital as novel substrates due to the presence of structurally homologous transporting proteins as in enterocytes. This phenomenon suggests the microbiome as a potential candidate that can significantly alter the pharmacokinetics of drugs.